Determinan Ketahanan Pangan di Indonesia : Pendekatan Data Panel - Nisa, Nur Ainun; Lubis, Firsty Ramadhona Amalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Although Indonesia holds the status of an agrarian country, it is still surrounded by food security issues. Data released by the FAO shows that Indonesia has at least 22.9 million people affected by hunger. Moreover, Indonesia ranks far below in terms of the food security index, ranking 63 out of 113 countries. This research aims to conduct a scientific analysis of the factors influencing food security in Indonesia. The research method used is the Fixed Effect Model (FEM) with longitudinal data dimensions from 2019 to 2021. The results of this study indicate that all independent variables collectively have a significant and simultaneous impact on food security. Partially, rice harvest area has a positive and significant effect on food security, rice production quantity has a positive and significant effect on food security, per capita food consumption has a positive and significant effect on food security, while Gross Regional Domestic Product (GRDP) per capita does not have a significant effect. Further research is expected to utilize other analytical tools and broader observations